Chagra y caney propuesta de escenario de reflexión y peregrinación cultural, a través del uso de las plantas sagradas en la plaza de mercado la perseverancia (2021)
The ways of thinking have been given from an imposition of hegemonic, systematic and linear knowledge, proof of this, are the studies carried out by the Colombian anthropologist Arturo Escobar, who affirms that the concept of development has not been more than a process of accumulation of capital and technical progress and is an economic, capitalist, imperial and cultural project that "arises from the particular experience of European modernity and subordinates other cultures and knowledge" (Escobar, 2013). This description of "development" could be related to the traditional practices of industrial design based on models of consumption, massification and currency exchange.